Manufacture, Characterization, and Release Profiles of Insulin-Loaded Mesoporous PLGA Microspheres. Issue 8 (10th June 2016) - Shi, Yongli; Ma, Suying; Tian, Ruiqiong; Zhao, Yingge; Cai, Fangyu; Li, Ranran; Shang, Qing
Abstract : This paper reports the fabrication of insulin-loaded mesoporous microspheres by a double emulsion-solvent evaporation technique using poly(lactic acid-co-glycolic acid) (PLGA) as carrier materials. PLGA solutions with two different concentrations (4% and 5%) were used as the oil phases to fabricate the mesoporous microspheres. The morphology and the particle size distribution of final microspheres were studied by optical microscope, scanning electronic microscope (SEM), and Malvern 2600 sizer, respectively. The mesoporous microspheres were monodisperse with an average diameter of 7 ± 3.5 µm. Insulin, as a model drug, was encapsulated into the final microspheres. In vitro release studies suggested that insulin was continuously released from the medicated microspheres. Furthermore, the final microspheres obtained from 4% PLGA solution showed a small "burst release" effect for their dense structures, which shortened the lag time to the effective plasma concentration. To summarize, the insulin-loaded PLGA microsphere are very promising for use in pharmaceutical applications.